Familial Atypical Hemolytic Uremic Syndrome: A Review of Its Genetic and Clinical Aspects - Fengxiao Bu; Nicolo Borsa; Ardissino Gianluigi; Richard J. H. Smith (Clinical and Developmental Immunology)
Atypical hemolytic uremic syndrome (aHUS) is a rare renal disease (two per one million in the USA) characterized by microangiopathic hemolytic anemia, thrombocytopenia, and acute renal failure. Both sporadic (80% of cases) and familial (20% of cases) forms are recognized. The study of familial aHUS has implicated genetic variation in multiple genes in the complement system in disease pathogenesis, helping to define the mechanism whereby complement dysregulation at the cell surface level leads to both sporadic and familial disease. This understanding has culminated in the use of Eculizumab as first-line therapy in disease treatment, significantly changing the care and prognosis of affected patients. However, even with this bright outlook, major challenges remain to understand the complexity of aHUS at the genetic level. It is possible that a more detailed picture of aHUS can be translated to an improved understanding of disease penetrance, which is highly variable, and response to therapy, both in the short and long terms.